Advancing DEI in research publishing – putting strategy into practice - Sule, Sam; Dunne, Maeve (Septentrio Conference Series, 2022)
In September 2021, Springer Nature made a formal commitment to Diversity, Equity & Inclusion (DEI) across our external Research & Solutions activities. Since then, our journals, books and magazines are elevating issues of diversity, representation, equity, justice and much more in both their content and their processes. From launching the industry’s first guide to content that may be harmful to human population groups, a new approach to ethics dumping and helicopter research, a transgender name change policy and Nature’s first ever guest edition on racism in science: we’ve taken steps to integrate DEI into the way we work and the content we create. This poster will talk about our experience so far turning strategy into practice, and the projects we’re planning for the near future from language guides to data collection.